Copper nanoclusters with strong fluorescence emission as a sensing platform for sensitive and selective detection of picric acid. Issue 35 (22nd August 2018) - Zhang, Wen Jie; Liu, Shi Gang; Han, Lei; Ling, Yu; Liao, Liu Li; Mo, Shi; Luo, Hong Qun; Li, Nian Bing
Abstract : The detection of picric acid has been developed based on a combined effect of molecular interactions and inner filter effect. Abstract : A facile, low-cost, and effective sensing strategy for detection of picric acid (PA) was developed based on copper nanoclusters (CuNCs). In this strategy, highly fluorescent CuNCs were prepared by using copper nitrate and ascorbic acid through an environmentally friendly process. Also, the PA-induced fluorescence quenching mechanism was investigated through ultraviolet-visible absorption spectra, fluorescence spectra, and fluorescence lifetimes, and might be ascribed to the molecular interactions and the strong inner filter effect between the CuNCs and PA. Under the optimal conditions, the fluorescence quenching degree of as-synthesized CuNCs was linearly dependent on the concentration of PA within a wide linear range of 2–40 μM, and the limit of detection was 0.98 μM. Finally, the proposed method was successfully applied to detect the levels of PA in real water samples.